PHYTOCHEMICAL SCREENING AND HEAVY METAL ANALYSIS OF ULVA RETICULATA - K, Gomathi; Sheba L, Anna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Ulva reticulata is a marine edible green seaweed widely distributed along the coastal lines of India. The present study was designed to screen the phytochemicals and evaluate heavy metals content of U. reticulata collected from Rameshwaram, Tamil Nadu, India, in the perspective of assessing their therapeutic value and/or safety in relation to its uses. Method: The seaweed sample was subjected to extraction with solvents of different polarities (methanol, ethanol, acetone, chloroform, and petroleum ether) and screened for phytochemicals according to standard methods. Heavy metal analysis was also performed with the dried sample powder using inductively coupled plasma optical emission spectrophotometer (ICP-OES). Result: Preliminary phytochemical analysis revealed the presence of reducing sugar, proteins, flavonoids, glycosides, alkaloids, and anthraquinones. ICP-OES indicated the seaweed to contain relative amount of heavy metals in the order of iron (Fe) > chromium (Cr) > Zinc (Zn) > nickel (Ni) > copper (Cu) > lead (Pb) - cadmium (Cd) and is within the permissible limits set by the WHO/FAO, except Fe and Cr. Conclusion: The different solvent extracts of U. reticulata showed the presence of the number of phytochemicals. Furthermore, the present study has revealed the presence of heavy metals in U. reticulata which can be a representative picture of the dissolved metals in the aquatic phase.